PEMANFAATAN TEKNOLOGI INFORMASI UNTUK BISNIS ONLINE PRODUK DIGITAL - Riska Riska; Lena Elfianty; Devi Sartika; Ahmad Arib Alfarisy; Muhammad Bintang Firdaus (Smart Education, 2024)
Abstract: This community service activity aims to improve the knowledge and skills of students at SMA Negeri 03 Bengkulu Utara in utilizing information technology for online business. Before the training, a pretest was conducted to measure the participants' initial knowledge, which showed that most participants had a low basic understanding before the training, with only 30% of participants successfully answering with a score of more than 60% of the total questions correctly. However, after the implementation of the training program, the posttest results showed a significant increase, where the average score of participants increased to 57% successfully answering with a score above 70% and 43% of participants successfully answering with a score of more than 80%. Feedback from participants showed that they felt more confident in applying this new knowledge in their business practices. Thus, this program provides direct benefits to students and contributes to the development of skills that are relevant to market needs in the digital era. It is hoped that similar activities can be continued in the future with more in-depth and diverse materials, as well as post-training mentoring support. Through a systematic and participatory approach, this program is expected to continue to support the development of student competencies in the fields of information technology and entrepreneurship, as well as provide a positive impact on society as a whole. Keyword: Information Technology, Online Business, Digital Products. Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan siswa di SMA Negeri 03 Bengkulu Utara dalam pemanfaatan teknologi informasi untuk bisnis online. Sebelum pelatihan, dilakukan pretest untuk mengukur pengetahuan awal peserta, yang menunjukkan bahwa sebagian besar peserta memiliki pemahaman dasar yang rendah sebelum pelatihan, dengan Hanya 30% peserta yang berhasil menjawab dengan skor lebih dari 60% dari total pertanyaan dengan benar. Namun, setelah pelaksanaan program pelatihan, hasil posttest menunjukkan peningkatan yang signifikan, di mana rata-rata skor peserta meningkat menjadi 57% berhasil menjawab dengan skor diatas 70% dan 43% peserta berhasil menjawab dengan skor lebih dari 80%. Umpan balik dari peserta menunjukkan bahwa mereka merasa lebih percaya diri untuk menerapkan pengetahuan baru ini dalam praktik bisnis mereka. Dengan demikian, program ini memberikan manfaat langsung bagi siswa dan berkontribusi pada pengembangan keterampilan yang relevan dengan kebutuhan pasar di era digital. Diharapkan kegiatan serupa dapat dilanjutkan di masa depan dengan materi yang lebih mendalam dan beragam, serta dukungan pendampingan pasca pelatihan. Melalui pendekatan yang sistematis dan partisipatif, program ini diharapkan dapat terus mendukung pengembangan kompetensi siswa di bidang teknologi informasi dan kewirausahaan, serta memberikan dampak positif bagi masyarakat secara keseluruhan. Kata kunci: Teknologi Informasi, Bisnis Online, Produk Digital.